A high-performance self-powered photodetector based on WSe2–graphene–MoTe2 van der Waals heterojunctions. Issue 24 (16th June 2022) - Feng, Pu; He, Sixian; Zhao, Sixiang; Dang, Congcong; Li, Ming; Zhao, Liancheng; Lu, Hong-Liang; Gao, Liming
Abstract : The introduction of a graphene interlayer contributes to an ultrafast and high-responsivity self-powered photodetector using a WSe2 –graphene–MoTe2 van der Waals heterojunction. Abstract : Self-powered photodetectors can detect light without an external power supply, which is critical for low-power applications and energy conservation. However, achieving high performance self-powered photodetectors remains a challenge. In this paper, we constructed a new WSe2 –graphene–MoTe2 van der Waals heterojunction-based self-powered photodetector. This self-powered device shows excellent photoresponse to 550 nm light (10 mW cm −2 ) with a responsivity of 40.84 mA W −1 and a detectivity of 1.21 × 10 11 Jones at zero bias. Moreover, it has an on/off ratio of 10 3 and a photoresponse time on the order of μs under a 520 nm laser (1 μW) at zero bias. We believe that the dual-Schottky junction heterojunction enables a promising approach for designing self-powered photodetectors.